Impact of Orthodontic Aligner Treatment on Oral Health-Related Quality of Life - Kabir Suman Dash; Osric DCosta; Ashwini Dhopte; Shivani Kumari; Mrunal Dave; Hiroj Bagde; Mahesh Ghadage; Dipooja Patil; Ramanpal Singh Makkad (Journal of Pharmacy and Bioallied Sciences)
Background: Orthodontic aligners have gained popularity due to their aesthetic appeal and convenience compared to traditional braces. Materials and Methods: One hundred patients (aged 18 to 30 years) receiving aligner-assisted orthodontic treatment participated in a prospective trial. The oral health impact profile-14 (OHIP-14) questionnaire was filled out by participants at baseline, three months, and six months during the course of therapy. Functional limits, pain, psychological discomfort, physical impairment, and social consequences were among the variables that were evaluated. Paired t-tests were used in statistical studies to assess how OHRQoL changed over time. Results: At three months, 60% of participants reported significant improvement in psychological comfort, with an average OHIP-14 score reduction from 25.4 ± 3.5 to 18.7 ± 2.9 (P < 0.001). Functional limitations decreased by 30% at six months, showing a significant improvement in chewing and speech, with mean scores dropping from 15.6 ± 2.1 to 11.3 ± 2.3 (P < 0.05). Social impact scores also improved by 25%, with participants reporting fewer disruptions in social interactions and self-consciousness. Conclusion: Orthodontic aligners positively impact the oral health-related quality of life of patients, particularly by enhancing psychological comfort and reducing functional limitations. This suggests that aligners are an effective orthodontic treatment option for patients seeking improvements in both aesthetic and quality-of-life aspects.